Two Element Microstrip Antenna Array with Defected Ground Structure - Zulkifli, Fitri Yuli; Rahardjo, Eko Tjipto; Asvial, Muhamad; Hartanto, Djoko (UI Scholars Hub, 2008)
Two Element Microstrip Antenna Array with Defected Ground Structure. This paper presents a two element microstrip antenna array using trapezium shape defected ground structure (DGS). The DGS is inserted in the ground plane between two elements of antenna array. Insertion of the DGS is intended to suppress the mutual coupling effect produced by antenna array. Simulation and measurement results were taken and compared between antenna array with and without DGS. Measurement results show that the antenna with DGS compared to antenna without DGS can suppress mutual coupling effect to 7.9 dB, improve the return loss to 33.29% from -30.188 dB to -40.24 dB and axial ratio bandwidth enhancement to 10 MHz. This bandwidth enhancement is achieved from frequency 2.63 GHz – 2.67 GHz for antenna without DGS and from frequency 2.63 GHz – 2.68 GHz for antenna with DGS. In addition, the DGS antenna also improved the antenna gain to 0.6 dB. The results show that the implementation of the trapezium DGS can improve the radiation properties of the antenna without DGS.